The Effect Of Brewing Technique On Sensory Testing Of Arabica And Robusta Coffee - Riris Kindeng Situmorang (JURAGAN - Jurnal Agroteknologi, 2025)
Coffee is an agricultural commodity with high economic value which plays an important role as a source of foreign exchange for the country. Two types of coffee that are widely known are Arabica and Robusta coffee, each of which has unique characteristics. Arabica coffee is known for its more sour taste and fragrant aroma, while Robusta coffee has a stronger taste and higher caffeine content. Brewing coffee affects the resulting sensory characteristics, which can be influenced by the brewing technique used. This research aims to test the sensory differences between Arabica and Robusta coffee using three manual brewing techniques, namely Siphon, French Press, and Moka Pot. Manual brewing techniques differ in the extraction method, where the Siphon uses steam pressure to extract coffee, the French Press with immersion to extract maximum coffee, and the Moka Pot uses steam pressure to produce concentrated coffee. This research measures the sensory characteristics of coffee based on taste, aroma, body, acidity and aftertaste produced by each brewing technique. The research results showed that the brewing technique had a significant impact on the sensory properties of Arabica and Robusta coffee.